Reasons that led hypertensive elderly to seek assistance in primary care - Roberta Fernanda Rogonni Ferrari; Daysi Mara Murio Ribeiro; Fabiana Cristina Vidigal; Sonia Silva Marcon; Vanessa Denardi Antoniassi Baldissera; Ligia Carreira (Universidade Federal do Ceará, 2014)
This study aimed to verify the complaints causing elderly hypertensive patients to seek a health center in a municipality of the state of Paraná, Brazil. Analytical and exploratory retrospective study conducted between November 2013 and January 2014, with 106 medical records of hypertensive elderly who attended nursing consultations in the past five years. Female elderly (73.5%), aged up to 70 years (61.3%), with a partner (57.5%) and with up to 4 years of education (73.5%) composed most of the sample. The main complaints causing elderly hypertensive patients to seek health care focused on endocrine and nutritional diseases (36%). There was significant association between gender and seeking the health service, with hypertension as major complaint, but no association was observed between complaints related to hypertension and number of interventions prescribed by nurses. The data revealed enable the planning of specific interventions to the needs of hypertensive elderly, allowing adjustments in care.